Taxes and the valuation of dividends: a study of dividend announcements in Germany - Christian Haesner; Deborah Schanz (Arbeitskreis Quantitative Steuerlehre (arqus), 2011)
This paper investigates the impact of the 2001 tax reform in Germany on dividend announcement returns. With this major tax reform, the full imputation system was replaced by the half-income system, which had a significant impact on the relative taxation of dividends and capital gains for most investor classes. In an event study framework, we separate the tax effect of dividends from their positive signaling and agency cost effects to offer a more comprehensive picture of the valuation implications of dividends in Germany. Controlling for signaling and agency cost effects of dividends we find that the market response to positive dividend surprises is more pronounced under the full imputation system, where dividends are generally more favorable to investors from a tax perspective, than under the half-income system. Our results suggest that the observed decline in the dividend response coefficient is synchronized with the 2001 tax reform and hence attributable to the 2001 tax reform.
Keywords: G35; G14; H3; G34; 330; Dividend Announcements; Taxation